Experiences of neurodivergent students in graduate STEM programs - Syharat, Connie Mosher; Hain, Alexandra; Zaghi, Arash E.; Gabriel, Rachael; Berdanier, Catherine G. P. (Frontiers in Psychology, 2023)
Introduction Despite efforts to increase the participation of marginalized students in Science, Technology, Engineering, and Mathematics (STEM), neurodivergent students have remained underrepresented and underserved in STEM graduate programs. This qualitative study aims to increase understanding of the experiences of neurodivergent graduate students pursuing advanced degrees in STEM. In this analysis, we consider how common graduate school experiences interface with the invisibility of neurological diversity, thus contributing to a set of unique challenges experienced by neurodivergent students. Materials and methods In this qualitative study, 10 focus group sessions were conducted to examine the experiences of 18 students who identify as neurodivergent in graduate STEM programs at a large, research-intensive (R1) university. We used thematic analysis of the transcripts from these focus groups to identify three overarching themes within the data. Results The findings are presented through a novel model for understanding neurodivergent graduate STEM student experiences. The findings suggest that students who identify as neurodivergent feel pressure to conform to perceived neurotypical norms to avoid negative perceptions. They also may self-silence to maintain stability within the advisor-advisee relationship. The stigma associated with disability labels contributes a heavy cognitive and emotional load as students work to mask neurodiversity-related traits, navigate decisions about disclosure of their neurodivergence, and ultimately, experience significant mental health challenges and burnout. Despite these many challenges, the neurodivergent graduate students in this study perceived aspects of their neurodivergence as a strength. Discussion The findings may have implications for current and future graduate students, for graduate advisors who may or may not be aware of their students’ neurodivergence, and for program administrators who influence policies that impact the wellbeing and productivity of neurodivergent students.